2019
DOI: 10.1182/blood-2018-12-891408
|View full text |Cite
|
Sign up to set email alerts
|

A cytosine-rich splice regulatory determinant enforces functional processing of the human α-globin gene transcript

Abstract: The establishment of efficient and stable splicing patterns in terminally differentiated cells is critical to maintenance of specific functions throughout the lifespan of an organism. The human α-globin (hα-globin) gene contains 3 exons separated by 2 short introns. Naturally occurring α-thalassemia mutations that trigger aberrant splicing have revealed the presence of cryptic splice sites within the hα-globin gene transcript. How cognate (functional) splice sites are selectively used in lieu of these cryptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Based on the fluorescence-based splicing reporter, the experimental approach was developed to systematically identify SREs [41]. The genome-wide discovery of SREs have been significantly advanced by combining the high-throughput sequencing with immunoprecipitation, such as the crosslinking immunoprecipitation sequencing (CLIP-seq) and RNA immunoprecipitation sequencing (RIP-seq) [42,43,44]. On the whole, hundreds of SREs have been computationally or experimentally discovered and most of them are mainly involved in regulating tissue-specific alternative splicing of pre-mRNAs [45].…”
Section: Sequence Features Of Alternative Exonsmentioning
confidence: 99%
“…Based on the fluorescence-based splicing reporter, the experimental approach was developed to systematically identify SREs [41]. The genome-wide discovery of SREs have been significantly advanced by combining the high-throughput sequencing with immunoprecipitation, such as the crosslinking immunoprecipitation sequencing (CLIP-seq) and RNA immunoprecipitation sequencing (RIP-seq) [42,43,44]. On the whole, hundreds of SREs have been computationally or experimentally discovered and most of them are mainly involved in regulating tissue-specific alternative splicing of pre-mRNAs [45].…”
Section: Sequence Features Of Alternative Exonsmentioning
confidence: 99%
“…In this issue of Blood, Ji et al have identified a novel regulatory mechanism that ensures proper splicing of human a-globin pre-messenger RNA (pre-mRNA). 1 One could be forgiven for thinking that splicing of this well-studied gene is fully understood, but Ji et al have described an essential new element: a C-rich sequence located a few nucleotides downstream of the intron 1 splice donor site that favors proper splicing while suppressing use of a competing cryptic splice site in the exon (see figure). Moreover, they report that polyC-binding proteins must interact with this intronic element to enhance proper splicing.…”
mentioning
confidence: 99%
“…10 In this issue of Blood, Pemmaraju et al explored the potential correlation between therapy with JAK inhibitors and the risk of a subsequent lymphoma in patients with myeloproliferative neoplasms (MPNs). 1 MPNs are clonal disorders complicated by vascular events, myelofibrosis, transformation to leukemia and, more rarely, the development of secondary malignancies. 2 Lymphoproliferative neoplasms (LPNs) in patients with MPNs are rare but occur at a higher frequency than that found in the general population.…”
mentioning
confidence: 99%